Pelatihan Kerajinan Ecoprint untuk Pengembangan Kreativitas Ibu dan Anak di Kelurahan Tanjung Gading - Sri Wilda Albeta; Abdullah, Abdullah; Sri Haryati; Putri Adita Wulandari; Novia Cristi Br Pasaribu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The ecoprint training held in Tanjung Gading Village aims to develop creativity, environmental awareness, and increase self-confidence among local mothers and children. This activity was carried out in three sessions on August 2, 3, and 18, 2024, and successfully involved 50 participants, including mothers from gymnastics groups, local mothers, and children. This training focused on the use of natural materials such as leaves and flowers to print unique patterns on fabrics, as well as promoting environmentally friendly practices. The results of the training showed a significant increase in the understanding and application of ecoprint techniques by participants. Before the training, 92% of participants were not familiar with this technique, but after the session, many showed increased ability and creativity in applying ecoprint. Feedback from participants was very positive, reflecting high satisfaction with the learning experience and the quality of their work. This training not only empowered the local community with new skills but also strengthened social relationships and increased environmental awareness. The success of this program confirms the potential of ecoprint workshops to make a significant contribution to local economic development and environmental sustainability. It is hoped that this activity can be a model for similar initiatives in other areas to advance creativity while supporting environmental conservation.